2002
DOI: 10.1002/mds.10252
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term efficacy of botulinum toxin A in treatment of various movement disorders over a 10‐year period

Abstract: Although botulinum toxin A (BTX) has been licensed in Canada for treatment of various movement disorders since 1990, few clinical studies regarding its long-term efficacy and side effects have been reported. We conducted a retrospective analysis of 235 patients who received BTX from our movement disorders clinic over a 10-year period (January 1990 to December 1999). A total of 2,616 treatment cycles (multiple injections) were administered to 235 patients with cervical dystonia (CD), hemifacial spasm (HS), blep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

19
144
4
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(174 citation statements)
references
References 30 publications
19
144
4
7
Order By: Relevance
“…Another important factor associated with patients giving up treatment that should be taken into consideration in our study is that it was carried out in a public hospital, a factor in developing countries that makes it more difficult to obtain suitable treatment regularly because of a range of situations related to patients' socioeconomic conditions. Other possibilities that should be considered are that patients may have continued the follow-up in different hospitals or died 8,9,13 . Among patients who underwent regular clinical follow-up, the rate of attendance at medical appointments was similar to that observed in studies in which a high degree of satisfaction with the long-term results of CD treatment with BoNT/A was reported 8,12,15 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another important factor associated with patients giving up treatment that should be taken into consideration in our study is that it was carried out in a public hospital, a factor in developing countries that makes it more difficult to obtain suitable treatment regularly because of a range of situations related to patients' socioeconomic conditions. Other possibilities that should be considered are that patients may have continued the follow-up in different hospitals or died 8,9,13 . Among patients who underwent regular clinical follow-up, the rate of attendance at medical appointments was similar to that observed in studies in which a high degree of satisfaction with the long-term results of CD treatment with BoNT/A was reported 8,12,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Among patients who underwent regular clinical follow-up, the rate of attendance at medical appointments was similar to that observed in studies in which a high degree of satisfaction with the long-term results of CD treatment with BoNT/A was reported 8,12,15 . BoNT/A is currently the treatment of choice for CD, and the results of long-term follow-up studies have shown the safety and efficacy of this treatment 6,8,9,12,13,15 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations